A study on patterns of needle - stick injuries among gynaecologic and general surgeons in open surgery - Chadha, Abhinav; Verma, Ashok; ., Sapna (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: An estimated 3,84,000 percutaneous injuries are reported by HCW in hospitals in the United States each year, placing them at risk of exposure to HIV, HBV, or HCV. Suture needles have been identified as the most frequent cause of injury. They are involved in as many as 44% of such injuries. This study is designed to note the NSI in major gynaecological procedures and surgical procedures using conventional method (CM) versus (VS) use of HK. Methods: Study was conducted over a period of 12 months from January 2017 to December 2017. 60 patients were included in this study and were divided into 2 groups A and B with 30 patients in each group. Group A was major surgery performed by conventional method; Group B was major surgery performed by using harmonic knife. NSI in two groups were studied and analyzed. Results: Most of the operated patients were between 41-50 years age group. 16.6% procedures were emergency and 83.3% were elective. NSI in conventional surgery was 63.3% in the surgeon and 33.3% with harmonic knife. There were 13.3% NSI in first assistant in conventional surgery and 23.3% in harmonic scalpel group. No such injuries were reported by second assistant in either group. Injuries were more in non-dominant hand in either groups in the surgeon and first assistant. Conclusions: It is concluded that NSI are common in surgeons and first assistant. Such injuries are more in non-dominant hand and in procedures where there is little exposure like vaginal hysterectomy. Use of innovative technologies like harmonic scalpel may be useful.